Phytohormone cytokinin guides microtubule dynamics during cell progression from proliferative to differentiated stage - Montesinos, Juan Carlos; Abuzeineh, Anas; Kopf, Aglaja; Juanes-Garcia, Alba; Ötvös, Krisztina; Petrášek, Jan; Sixt, Michael; Benková, Eva (The EMBO journal, 2020)
Cell production and differentiation for the acquisition of specific functions are key features of living systems. The dynamic network of cellular microtubules provides the necessary platform to accommodate processes associated with the transition of cells through the individual phases of cytogenesis. Here, we show that the plant hormone cytokinin fine-tunes the activity of the microtubular cytoskeleton during cell differentiation and counteracts microtubular rearrangements driven by the hormone auxin. The endogenous upward gradient of cytokinin activity along the longitudinal growth axis in Arabidopsis thaliana roots correlates with robust rearrangements of the microtubule cytoskeleton in epidermal cells progressing from the proliferative to the differentiation stage. Controlled increases in cytokinin activity result in premature re-organization of the microtubule network from transversal to an oblique disposition in cells prior to their differentiation, whereas attenuated hormone perception delays cytoskeleton conversion into a configuration typical for differentiated cells. Intriguingly, cytokinin can interfere with microtubules also in animal cells, such as leukocytes, suggesting that a cytokinin-sensitive control pathway for the microtubular cytoskeleton may be at least partially conserved between plant and animal cells.
Keywords: buněčná diferenciace; mikrotubuly; Cytokinins; Arabidopsis; Animals; microtubules dynamics; cell differentiation; cytoskeleton; Plant Roots; kořeny rostlin; Microtubules; microtubules; zvířata; proliferace buněk; cytokinin; Cell Proliferation; Cell Differentiation; cytokininy